Comparative and Phylogenetic Analysis Based on the Chloroplast Genome of Coleanthus subtilis (Tratt.) Seidel, a Protected Rare Species of Monotypic Genus - Ren, Jing; Tian, Jing; Jiang, Hui; Zhu, Xin-Xin; Mutie, Fredrick Munyao; Wanga, Vincent Okelo; Ding, Shi-Xiong; Yang, Jia-Xin; Dong, Xiang; Chen, Ling-Ling; Cai, Xiu-Zhen; Hu, Guang-Wan (Frontiers in Plant Science, 2022)
Coleanthus subtilis (Tratt.) Seidel (Poaceae) is an ephemeral grass from the monotypic genus Coleanthus Seidl, which grows on wet muddy areas such as fishponds or reservoirs. As a rare species with strict habitat requirements, it is protected at international and national levels. In this study, we sequenced its whole chloroplast genome for the first time using the next-generation sequencing (NGS) technology on the Illumina platform, and performed a comparative and phylogenetic analysis with the related species in Poaceae. The complete chloroplast genome of C. subtilis is 135,915 bp in length, with a quadripartite structure having two 21,529 bp inverted repeat regions (IRs) dividing the entire circular genome into a large single copy region (LSC) of 80,100 bp and a small single copy region (SSC) of 12,757 bp. The overall GC content is 38.3%, while the GC contents in LSC, SSC, and IR regions are 36.3%, 32.4%, and 43.9%, respectively. A total of 129 genes were annotated in the chloroplast genome, including 83 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. The accD gene and the introns of both clpP and rpoC1 genes were missing. In addition, the ycf1, ycf2, ycf15, and ycf68 were pseudogenes. Although the chloroplast genome structure of C. subtilis was found to be conserved and stable in general, 26 SSRs and 13 highly variable loci were detected, these regions have the potential to be developed as important molecular markers for the subfamily Pooideae. Phylogenetic analysis with species in Poaceae indicated that Coleanthus and Phippsia were sister groups, and provided new insights into the relationship between Coleanthus, Zingeria, and Colpodium. This study presents the initial chloroplast genome report of C. subtilis, which provides an essential data reference for further research on its origin.